2018
DOI: 10.3390/nu10081055
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Intestinal Fermentation of Natural Polysaccharides

Abstract: With the rapid development of modern society, many chronic diseases are increasing including diabetes, obesity, cardiovascular diseases, etc., which further cause an increased death rate worldwide. A high caloric diet with reduced natural polysaccharides, typically indigestible polysaccharides, is considered a health risk factor. With solid evidence accumulating that indigestible polysaccharides can effectively prevent and/or ameliorate symptoms of many chronic diseases, we give a narrative review of many natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 196 publications
(204 reference statements)
1
111
0
Order By: Relevance
“…These results are in line with those obtained by Kalyan et al () as they reported that the MPs significantly lowered plasma and liver cholesterol and TAGs. In a similar mechanism as the Colocasia esculenta 's and the Abelmoschus esculentus ' mucilage (Chukwuma, Islam, & Amonsou, ) Cymodocea nodosa 's mucilage (Zhang, Yang, Liang, Jiao, & Zhao, ) and related Ziziphus mauritana (Deshpande et al, ) and Ziziphus jujuba 's mucilage (Ganachari, Kumar, & Alagawadi, ), Nabq mucilage (Table ) diminished lipid absorption at the intestinal level by inhibiting the activity of pancreatic lipase (Elbashir et al, ), scoring as the second best inhibitor among 18 dietetic plants. Dechakhamphu and Wongchum (), as Tan et al () went deeper to arraign plant phenolics (within identical mucilages) as potent inhibitors of carbohydrate digesting enzymes, namely phenolic acids like ferulic acid (and other phenolic acids like p‐coumarin, p‐hydroxybenzoic acid, and syringic acid or phenolic esters like chlorogenic acid); Ghafoor, Qadir, and Fakhri () found ferulic acid in the NabM as well as phenolic compounds like rutin, apigenin, and quercetin.…”
Section: Resultsmentioning
confidence: 96%
“…These results are in line with those obtained by Kalyan et al () as they reported that the MPs significantly lowered plasma and liver cholesterol and TAGs. In a similar mechanism as the Colocasia esculenta 's and the Abelmoschus esculentus ' mucilage (Chukwuma, Islam, & Amonsou, ) Cymodocea nodosa 's mucilage (Zhang, Yang, Liang, Jiao, & Zhao, ) and related Ziziphus mauritana (Deshpande et al, ) and Ziziphus jujuba 's mucilage (Ganachari, Kumar, & Alagawadi, ), Nabq mucilage (Table ) diminished lipid absorption at the intestinal level by inhibiting the activity of pancreatic lipase (Elbashir et al, ), scoring as the second best inhibitor among 18 dietetic plants. Dechakhamphu and Wongchum (), as Tan et al () went deeper to arraign plant phenolics (within identical mucilages) as potent inhibitors of carbohydrate digesting enzymes, namely phenolic acids like ferulic acid (and other phenolic acids like p‐coumarin, p‐hydroxybenzoic acid, and syringic acid or phenolic esters like chlorogenic acid); Ghafoor, Qadir, and Fakhri () found ferulic acid in the NabM as well as phenolic compounds like rutin, apigenin, and quercetin.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, an overview of the main polysaccharides, including their potential food and medical applications, is presented in Table 2. Depending on the single sugar moieties (glucose, galactose, fructose, mannose), polysaccharides are classified in two groups: (1) homo-polysaccharides, which contain only one kind of polymerized sugar unit like starch, xylan, galactan, and froctan, and (2) heteropolysaccharides, containing two or more kinds of sugar units such as pectin [186]. Polysaccharides, in many forms, play a central role in all living organisms for supply and storage of energy and/or structural integrity and protection of cells.…”
Section: Polysaccharides' Contribution To Healthmentioning
confidence: 99%
“…Many foods contain a great number of polysaccharides that cannot be completely digested by the digestive system. These indigestible polysaccharides can be called dietary fibers [186]. The class of polysaccharides such as pectin, inulin, and gums are able to slow the food movement in the digestive tract and to slow the sugar absorption from food into blood.…”
Section: Polysaccharides' Contribution To Healthmentioning
confidence: 99%
See 2 more Smart Citations